1989
DOI: 10.1037/0735-7044.103.3.605
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned taste aversions are not readily disrupted by external excitation.

Abstract: Thirsty male rats were given saccharin water followed by delayed illness. During the delay, some of the rats were exposed to events designed to stimulate their external systems (i.e., the system that processes external events such as auditory and tactile stimulation). Access to females, mild footshocks, and pain from hypertonic saline injections did not interfere with either the acquisition or extinction of a taste aversion. In fact, when administered intraperitoneally, the hypertonic saline slightly increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…The result indicated that associative learning between LiCl injection and xylene solution was the only factor inducing the CTA. Results in the present study are consistent with the study that examined effects of some events to stimulate animals' external systems as disruptions for establishing the CTA (Holder et al, 1989). In the study by Holder et al (1989), rats, given saccharin water followed by delayed illness, were exposed to events such as access to females, mild foot shocks, pain induced by intraperitoneal injection of hypertonic saline, and heat that changed both skin and core temperatures.…”
Section: Discussionsupporting
confidence: 88%
“…The result indicated that associative learning between LiCl injection and xylene solution was the only factor inducing the CTA. Results in the present study are consistent with the study that examined effects of some events to stimulate animals' external systems as disruptions for establishing the CTA (Holder et al, 1989). In the study by Holder et al (1989), rats, given saccharin water followed by delayed illness, were exposed to events such as access to females, mild foot shocks, pain induced by intraperitoneal injection of hypertonic saline, and heat that changed both skin and core temperatures.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, both a single session of 90 inescapable shocks and eight ses sions of 120 inescapable shocks attenuate LiCl CTA (Dess et al 1988;Revusky and Reilly 1989). In contrast to these results, however, two exposures to either hyper tonic saline injections or two footshocks does not alter LiCl CTA (Holder et al 1989). These results suggest that stressor parameters are, in fact, important in the attenua tion of LiCl CTA.…”
Section: Introductionmentioning
confidence: 77%
“…A number of studies have evaluated the influence of ex posure to stressors on the development and extinction of conditioned taste aversions (CTA) (Lasiter and Braun 1981;Dess et al 1988;Holder et al 1989;Revusky and Reilly 1989;Bourne et al 1992). These studies have re ported that exposure to stressors can decrease (Revusky and Reilly 1989;Bourne et al 1992), increase (Lasiter and Braum 1981) or do not affect CTA (Holder et al 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it is possible that adolescent animals experienced more stress given that they were given a shorter time to acclimate to the vivarium prior to the initiation of experimental procedures than their adult counterparts. Interestingly, the effects of stress on the development and expression of CTAs are mixed, with reports of stress potentiating CTAs (Bowers, Gingras, & Amit, 1996; Lasiter & Braun, 1981) and in some cases, stress having no effect (Bowers et al, 1996; Holder, Yirmiya, Garcia, & Raizer, 1989; Roma, Davis, Kohut, Huntsberry, & Riley, 2008). If the adolescent animals in the present assessment were under more stress, it might be expected that they would show stronger MDMA-induced aversions.…”
Section: Discussionmentioning
confidence: 99%